The use of Language In International Agreements According to The 1969 Vienna Convention And Its Implementation In Indonesian National Law - Elvardi, Jean; Hasan, Firman; Pratama, Arya Putra Rizal (Yuridika, 2022)
The use of language in international agreements is very important to establish international cooperation. It is also noteworthy that according to the Indonesian law, the international agreements related to several matters adopted by the government shall be translated to Bahasa Indonesia. However, the terms contained in Indonesian national law, in Bahasa Indonesia, often tend to be different from the meanings contained in international law, such as the 1969 Vienna Convention on the Law of Treaties. Thus, they often have multiple interpretations. As such, the use of language, especially relating to international agreements, can be a trigger for legal disputes. In this regard, using a legal research method by analyzing the international legal instruments and Indonesian national law, this paper digs into the use of language related to the adoption of an international agreement to an Indonesian Law, especially regarding the terms of "ratification,” "accession,”  and others. It is argued that there is a difference of perspective within the "adoption of an international agreement” regarding the terms of "ratification” and "accession” under the 1969 Vienna Convention.